A review of the current quality standards framework supporting forensic science: Risks and opportunities. Issue 3 (19th November 2019) - Doyle, Sean
Abstract: The publication and implementation of the latest editions of the International Organization for Standardization (ISO) 9001:2015 and ISO/International Electrochemical Commission (IEC) 17025:2017 together with the recent publication of the first book on quality management in forensic science provide an opportunity for this review. It details the changes to the structure, content and scope of the latest editions and assesses the impact on forensic science. Key terms are defined and explained. The review examines the effectiveness of the quality standards framework (QSF) supporting forensic science in the regions of Australia and New Zealand, Europe and North America. The concept of a hierarchy is introduced as a means of classifying standards to better navigate the crowded landscape. The main body of the review identifies risks to the QSF and opportunities for improvement. This article is categorized under: Forensic Science in Action/Crime Scene Investigation > Education and Formation Forensic Chemistry and Trace Evidence > Presentation and Evaluation of Forensic Science Output Jurisprudence and Regulatory Oversight > Expert Evidence and Narrative Forensic Biology > Interpretation of Biological Evidence Abstract : The quality standards framework supporting forensic science.